Sytuacje trudne w perspektywie jednostkowej i społecznej - (:unkn) unknown (Wydawnictwo Naukowe UAM, 2016)
The publication provides the reader with a clear description of difficult situations experienced by different individuals at different stages of their lives and in different environments. A difficult situation, therefore, can be regarded as a continuum, because on the one hand we are dealing with a problematic situation, and on the other with a state of mental stress. An individual can seek a constructive solution to a difficult situation, and therefore treat it as a task or challenge. There is also a possibility that the situation will become a stressful one, which will disrupt human behavior. Undoubtedly, the struggle with a variety of difficult life situations is a challenge for every individual. The diverse nature of these texts testifies to the complexity and importance of the issues. We therefore hope that readers will find in this publication some answers to their issues, guidance, or that the publication will become a source of inspiration for further theoretical and practical actions.

W publikacji poruszono problem człowieka uwikłanego w sytuacje trudne, zarówno w kontekście jednostki, jak i społeczeństwa. Sytuacje trudne rozpatrywane są przez pryzmat osoby uzależnionej od alkoholu, przebywającej w zakładzie karnym, a także ofiary przestępstwa, którą może być dziecko czy osoba starsza, osób z niepełnosprawnością oraz ich opiekunów. Książka zawiera również praktyczne metody i wskazówki, w jaki sposób ograniczyć psychospołeczne koszty ponoszone przez jednostkę doświadczającą traumatycznych przeżyć.
Difficult situations from the individual and societal perspective
Keywords: terapia uzależnień; adolescencja; czynniki ryzyka; czynniki ochronne; zachowania przestępcze; przemoc; dorosłość; sytuacje trudne; wykorzystanie seksualne; psychoterapia skoncentrowana na emocjach